Spatial effects of climate change on tourism development in china: An analysis of tourism value chains - Xiong, Na; Sun, Bingteng; Jiang, Linli; Cui, Haitao (Frontiers in Environmental Science, 2022)
Tourism value chains is scattered across the economic fields. This paper seeks to carry out an empirical analysis of the relationship between climate change and tourism development in China. We used relevant data from 31 provinces in China, and analyzed the spatial effects of climate change on tourism development using a spatial Durbin model. In the development of tourism in Chinese provinces, the research results show that the high-high agglomeration areas of inbound overnight tourists are widely distributed in the coastal areas of eastern China, while the low-low agglomeration areas are mainly distributed in western China, showing an unreasonable bipolar distribution. In terms of climate change, the increase of annual precipitation contributes to the enhancement of the number of inbound overnight tourists in local areas, but reduces the number of inbound overnight tourists in adjacent areas; the increase of annual average temperature raises the number of inbound overnight tourists in local areas, but decreases the number of inbound overnight tourists in adjacent areas; which indicates that there is a spatial spillover effect of climate change on tourism development. Therefore, we propose that western China should receive further policy support, the positive spatial spillover effect of the number of inbound overnight visitors among provinces should be fully utilized, and the tourist attractions should be enriched and developed. However, there are some limitations in the construction of the spatial weight matrix, the consideration of sample size, and the selection of factors affecting tourism development.